2023
DOI: 10.1186/s12882-023-03358-0
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and prognosis of patients with kidney transplantation: a meta-analysis

Jianming Zheng,
Yu Cao,
Zhen Wang
et al.

Abstract: Background The prevalence of frailty among candidates and recipients of kidney transplantation (KT) is well-established, yet the impact of frailty on clinical outcomes following KT remains uncertain. To address this knowledge gap, we conducted a systematic meta-analysis to comprehensively assess the aforementioned relationship. Methods The present study conducted a comprehensive search of PubMed, Embase, and Cochrane Library databases to identify r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The authors noted that the heterogeneity of methods for evaluating and diagnosing frailty was a limitation to their analysis, and that further study is needed to develop a gold-standard definition of frailty. 3 Delirium has also been associated with poor outcomes following kidney transplantation. 25 In a retrospective study of 35,800 kidney transplant recipients ≥55 years old, Ruck et al observed that risk factors for delirium in these patients included advanced age and diabetes mellitus.…”
Section: Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted that the heterogeneity of methods for evaluating and diagnosing frailty was a limitation to their analysis, and that further study is needed to develop a gold-standard definition of frailty. 3 Delirium has also been associated with poor outcomes following kidney transplantation. 25 In a retrospective study of 35,800 kidney transplant recipients ≥55 years old, Ruck et al observed that risk factors for delirium in these patients included advanced age and diabetes mellitus.…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…The authors noted that the heterogeneity of methods for evaluating and diagnosing frailty was a limitation to their analysis, and that further study is needed to develop a gold-standard definition of frailty. 3…”
Section: Kidney Transplantationmentioning
confidence: 99%